The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1055/s-2006-924524
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responses of Germination and Seedling Establishment in Populations of Tragopogon pratensis (Asteraceae)

Abstract: The establishment phase is an important bottleneck in the life cycle of plants. It consists of two steps that are rarely separated, i.e., the germination of seeds and the establishment of seedlings. Here we report the results of two experiments in which we independently investigated germination and seedling establishment in the greenhouse, under different grass vegetation treatments representing different regeneration niches. Seeds of Tragopogon pratensis from six populations and two habitat types were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…In Clarkia species, germination ability did not exhibit local adaptation, but postgermination survival did, although it is not clear the extent to which variation in germination phenology contributed to those differences in survival (Geber & Eckhart 2005). In Tragopogon pratensis, seeds from roadside populations germinated faster and to higher percentages when grown in roadside locations than did those from nonroadside populations ( Jorritsma-Wienk et al 2007). Bromus tectorum showed local adaptation in germination, operating through seedling survival, in low-elevation sites but not high-elevation sites (Leger et al 2009), andSzarek et al (1998) reported local adaptation in germination in Encelia farinose.…”
Section: Evidence Of Local Adaptation In Germinationmentioning
confidence: 95%
See 1 more Smart Citation
“…In Clarkia species, germination ability did not exhibit local adaptation, but postgermination survival did, although it is not clear the extent to which variation in germination phenology contributed to those differences in survival (Geber & Eckhart 2005). In Tragopogon pratensis, seeds from roadside populations germinated faster and to higher percentages when grown in roadside locations than did those from nonroadside populations ( Jorritsma-Wienk et al 2007). Bromus tectorum showed local adaptation in germination, operating through seedling survival, in low-elevation sites but not high-elevation sites (Leger et al 2009), andSzarek et al (1998) reported local adaptation in germination in Encelia farinose.…”
Section: Evidence Of Local Adaptation In Germinationmentioning
confidence: 95%
“…In Centaurea, burnt soil inhibited germination, even though the nutrient release from burning increased seedling growth; however, seedlings also grew better in shade, which would be eliminated by fire (Riba et al 2002). In other examples, germination showed some evidence of adaptation in terms of germination percentages, but seedling performance did not ( Jorritsma-Wienk et al 2007). In some cases, seeds tended to germinate in environments that were actually less favorable for seedling survival.…”
Section: The Integrated Organism: Associations Between Germination Anmentioning
confidence: 98%
“…The major reason of this variation during autumn and winter appeared to be seedlings mortality caused by both abiotic and biotic stresses such as cold temperatures, soil drought and intraspecific competition (Harper and McNaughton, 1962;Jorritsma-Wienk et al, 2007;White and Harper, 1970). Anyway, two years after sowing, only C.…”
Section: Accepted Papermentioning
confidence: 99%
“…In this respect, Jorritsma-Wienk et al (2006) andJongejans et al (2006) argue that the establishment phase represents the most important bottleneck in the life cycle of the plant species, which is divided into two parts: seed germination and plant survival. After successful establishment, positive (facilitation) and negative (competition) interaction play an important role in driving the overall plant species' assemblage (Callaway 2007).…”
Section: Introductionmentioning
confidence: 99%